Rare earth (Gd, La) co-doped ZnO nanoflowers for direct sunlight driven photocatalytic activity - Palanivel, Baskaran; Macadangdang, Romulo R.; Hossain, Md Shahadat; Alharthi, Fahad A.; Kumar, Mohanraj; Chang, Jih-Hsing; Gedi, Sreedevi (Journal of rare earths, 2023)
In this work Gd/La@ZnO nanoflower photocatalyst was successfully synthesized by a co-precipitation method and applied for rhodamine B (Rh B) and tetracycline (TCN) degradation under direct sunlight irradiation. The doping of rare earth elements extends the optical absorption wavelength of ZnO from UV region (390 nm) to visible-light region (401 nm). In addition, the co-doped ZnO nanoflower exhibits a lower charge recombination efficiency which was confirmed by photoluminescence emission analysis. Moreover, the co-doped ZnO nanoflower exhibits the maximum degradation efficiency of 91% for Rh B and 74% for TCN under sunlight irradiation. The calculated synergistic index of co-doped ZnO is higher than that of the pure ZnO. Reactive radicals' production was confirmed by terephthalic acid (TA) and nitro-blue tetrazolium (NBT) tests. The holes and hydroxyl (•OH) radicals play the major role in degradation reaction and it was confirmed by scavenger's test. Moreover, the recycling test confirms the stability of the photocatalyst. Highly active and stable rare earth (Gd and La) co-doped ZnO nanoflowers were prepared for photocatalytic organic pollutant degradation. [Display omitted]